IT integration in post-acquisition integration : The perspective of a serial cross-border acquirer - Forsström, Julia (My University, 2024)
Mergers and acquisitions (M&As) are a significant means of strategy formulation and strategic renewal, and information technology (IT) integration is one of the most challenging parts of the M&A process. IT integrations in M&As have been widely researched for over 30 years, but there have been calls to research this field of study more comprehensively. Prior research has extensively focused on single M&As, and the perspective of serial acquirers has largely been undermined. This thesis attempts to investigate this unexplored view by combining well-known and widely used post-acquisition and IT integration theories. Additionally, the study focused on cross-border acquisitions to see if IT integrations differ in a cross-border setting. The empirical part of the study was based on semi-structured interviews with professionals from serial cross-border acquirers. Existing literature on post-acquisition integration, IT integration and IT-business alignment were reviewed to form a comprehensive theoretical framework in which to examine the results of the study. The results of this study revealed that serial acquirers have limited options when it comes to IT integration methods to enable future acquisitions and integrations as well. The choice of IT integration method was found to be impacted by the overall M&A objectives and the post-acquisition integration strategy chosen to ensure IT and business operations and processes are aligned. In the cross-border context, taking into account the law and regulations and infrastructure of the target company’s home country was found to be more important that considering cultural distance. The study concludes that aligning IT and business through an appropriate choice of IT integration method is important. This ensures that IT supports both the internal operations and processes of the target and the shared operations of the acquirer and target. However, serial acquirers need to take into consideration the cost implications of different IT integration methods and the resources needed to maintain those integrations. Doing acquisitions cross-borders does not affect the choice of IT integration method but rather the execution of the integration through increasing complexity and extending the timetable. This should be taken into account when planning the IT integration. The IT integration methods found in previous literature do not cater for the needs of today’s acquirers and they should be revised to fit the data volume and system complexity requirements of the digital age.

Yrityskaupat ovat merkittävä strateginen työkalu, ja tietojärjestelmien integraatio (IT integraatio) on yksi yrityskauppaprosessin haastavimmista osista. Yrityskauppojen IT integraatioita on tutkittu laajalti jo 30 vuoden ajan, mutta ilmiötä on toivottu tutkittavan laaja-alaisemmin. Aiempi tutkimus on keskittynyt laajalti yksittäisiin yrityskauppoihin ja näin ollen jättänyt huomiotta sarjaostajien näkökulman. Tämä tutkielma yhdistelee yrityskauppojen ja tietojärjestelmien integraatioon liittyvää tieteellistä kirjallisuutta ja keskittyy tuottamaan uutta tietoa erityisesti sarjaostajan näkökulmasta. Tutkimus rajattiin sarjaostajiin, jotka tekevät ostoja sekä kotimaassa että kansainvälisesti, jotta voitiin selvittää, eroavatko rajojen yli tapahtuvat integraatiot kotimaisista. Tutkimus toteutettiin puolistrukturoiduilla haastatteluilla, joihin osallistui sekä suomalaisten että ulkomaalaisten sarjaostajien asiantuntijoita. Aiemman tutkimuksen pohjalta muodostettiin kokonaisvaltainen teoreettinen viitekehys, johon tutkimuksen tuloksia heijastettiin. Tulosten mukaan sarjaostajilla on valittavana rajallinen määrä IT integraatiometodeja, jotta mahdollistetaan myös tulevat yritysostot ja integraatiot. IT integraatiometodin valintaan vaikuttavat sekä yrityskaupan että yleisen integraation tavoitteet, jotta voidaan varmistaa, että IT ja liiketoiminnan prosessit ovat linjassa keskenään. Kansainvälisissä kaupoissa ostettavan yrityksen kotimaan lainsäädännöllä, säädöksillä sekä infrastruktuurilla on suurempi merkitys kuin maiden välisellä kulttuurisella välimatkalla. Tutkimuksen perusteella voitiin päätellä, että sopivan IT integraatiotavan valinta on tärkeää, jotta yrityksen IT ratkaisut ja liiketoiminnan prosessit ovat linjassa keskenään. Tämä varmistaa, että IT tukee sekä ostettavan yrityksen sisäisiä prosesseja että ostavan ja ostetun yrityksen jaettuja prosesseja. Sarjaostajien tulee kuitenkin ottaa myös huomioon eri IT integraatiometodien kustannukset sekä resurssit, joita integraation ylläpito vaatii. Yrityskaupan kansainvälisyydellä ei ole vaikutusta IT integraatiotavan valintaan, mutta se vaikuttaa integraation toteutukseen tekemällä toteutuksesta monimutkaisempaa ja pidentämällä aikatauluja. Tämä tulisi ottaa huomioon suunnitellessa IT integraatiota. Aiemmassa kirjallisuudessa löydetyt IT integraatiotavat eivät palvele nykyajan yrityskauppoja, ja niitä tulisi kehittää ottamaan huomioon nykypäivän datan määrä ja järjestelmien monimutkaisuus.
Keywords: information technology integration, IT integration, mergers and acquisitions, serial acquisition, IT-business alignment, cross-border acquisition, tietojärjestelmien integraatio, IT integraatio, yrityskaupat, sarjaostajat, yrityskauppaintegraatiot, IT:n ja liiketoiminnan linjaus, kansainväliset yrityskaupat